A putative endophytic Bacillus cereus str. S42 from Nicotiana glauca for biocontrol of Fusarium wilt disease in tomato and gas chromatography-mass spectrometry analysis of its chloroform extract. (26th August 2016) - Aydi Ben Abdallah, Rania; Nefzi, Ahlem; Jabnoun-Khiareddine, Hayfa; Messaoud, Chokri; Stedel, Catalina; Papadopoulou, Kalliope K.; Mokni-Tlili, Sonia; Daami-Remadi, Mejda
Abstract: A putative endophytic Bacillus cereus str. S42 (KP993206), recovered from surface-sterilised stems of Nicotiana glauca was assessed in vitro and in vivo for its antifungal potential towards Fusarium oxysporum f. sp. lycopersici (FOL). Pathogen sporulation was significantly inhibited by B. cereus str. S42. FOL mycelial growth was reduced using its whole-cell suspensions, cell-free culture supernatant and chloroform extract. Its extracellular metabolites remained effective after heating at 50–100 °C with a decline in their activity was observed beyond 100 °C, when added with proteinase K and/or after pH adjustment to 2 and 12. Chitinase gene was detected using PCR amplification. Gas chromatography–mass spectrometry analysis of its chloroform extract matched phthalic acid, dibutyl ester with high level of similarity. B. cereus str. S42 cell-free culture supernatant and whole-cell suspensions had significantly suppressed Fusarium wilt severity by 87–96% and enhanced tomato growth by 39–79% compared to FOL-inoculated and untreated control.